Time to Listen: Children s Voice in Geoscience Education Research - Roche, Joseph (My University, 2021)
Arguably the greatest threat facing society is that posed by irreversible climate change. Intandem with mitigating the effects of climate change, we must now make decisions aboutissues such as renewable energy, sustainable and safe water supplies, management ofrenewable and non-renewable natural resources, and management of natural disasters.The current school-age generation will see the worst effects of climate change, includinggreater frequency and intensity of extreme weather events; shortages of water and othernecessary resources; and dangers due to pollution and toxicity in human environmentsand the human food chain. The next generation is coming of age as difficult socio-politicalchoices are being made at local and national levels to manage resources and mitigateenvironmental damage. It is therefore important to center the voices of children and youngpeople in research aiming to address the social, political, and educational dimensions ofgeoscience topics, including climate change and related topics. This paper proposes theuse of Children’s Research Advisory Groups (CRAGs) to meaningfully include children andyoung people as co-researchers in geoscience-related research.
PUBLISHED
Keywords: climate education, children’s research advisory group, student voice, science communication, public engagement, climate change, science and society; Inclusive Society; Smart & Sustainable Planet; CLIMATE CHANGE; SCIENCE COMMUNICATION; Science and Society; Student Voice; climate education